Upaya Meningkatkan Hasil Belajar Siswa Kelas III Pada Materi Pancaindra Melalui Model Pembalajaran PBL Berbantu Media Flashcard - Dito Mei Triono; Nur Samsiyah; Budi Utomo (Asosiasi Riset Ilmu Pendidikan Indonesia, 2024)
By using a problem-based learning (PBL) model supported by flashcard media, classroom action research (CAR) was conducted in two cycles, with observation, reflection, implementation, and planning. The aim was to improve student learning outcomes in the five senses material in grade III. The results showed that, in the first cycle, 44% of students achieved completion, with an average score of 68%; in the second cycle, the percentage of completion increased to 86%, with an average score of 82%. These results indicate that the application of the PBL model with flashcard media can help students understand the five senses material better. As a result, this learning approach can be used as an alternative to improve the quality of learning in elementary schools.